The long‐term cost‐effectiveness of varenicline (12‐week standard course and 12 + 12‐week extended course) vs. other smoking cessation strategies in Canada. Issue 5 (29th January 2014) - von, M.; Raymond, V.; Paradis, P. E.
Summary Background Smoking is the leading risk factor for preventable morbidity and mortality as a result of heart and lung diseases and various forms of cancer. Reimbursement coverage for smoking cessation therapies remains limited in Canada and the United States despite the health and economic benefits of smoking cessation. Objectives This study aimed to evaluate the long‐term cost‐effectiveness of varenicline compared with other smoking cessation interventions in Canada using the Benefits of Smoking Cessation on Outcomes (BENESCO) model. Methods Efficacy rates of the standard course (12 weeks) varenicline, extended course (12 + 12 weeks) varenicline, bupropion, nicotine replacement therapy and unaided intervention were derived based on a published mixed treatment comparison methodology and analysed within a Markov cohort model to estimate their cost‐effectiveness over the lifetime cycle. Study cohort, smoking rates and prevalence, incidence and mortality of smoking‐related diseases were calibrated to represent the Canadian population. Results Over the subjects' lifetime, both the standard and the extended course of varenicline are shown to dominate (e.g. less costly and more effective) all other alternative smoking cessation interventions considered. Compared with the standard varenicline treatment course, the extended course is highly cost‐effective with an incremental cost‐effectiveness ratio (ICER) less than $4000 per quality‐adjusted life year. Including indirect cost and benefits of smoking cessation interventions further strengthens the result with the extended course of varenicline dominating all other alternatives considered. Limitations Evidence from complex smoking cessation models requiring numerous inputs and assumptions should be assessed in conjunction with evidence from other methodologies. Conclusions The standard and extended courses of varenicline are decidedly cost‐effective treatment regimes compared with alternative smoking cessation interventions and can provide significant cost savings to the healthcare system.